Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1016/j.jadohealth.2021.12.021
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Empathy in Chinese Adolescents’ Preventive Health Behavior During COVID-19

Abstract: Purpose Preventive health behavior during COVID-19 protects not only oneself but also the welfare of others. However, little attention has been paid to prosocial motivation in adolescents, who are often viewed as selfish and egocentric. Therefore, the current study aimed to explore the role of empathy in adolescents’ preventive health behavior using longitudinal data. Methods A total of 442 Chinese adolescents (mean age of youth = 13.35 years; 49.5% girls and 50.5% boys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 40 publications
2
12
0
8
Order By: Relevance
“…Under COVID-19 conditions, how to prevent health behavior (e.g., vaccination) is an important issue to be considered [ 76 ]. Besides personal factors such as beliefs and self-efficacy about preventive health behavior, there are views suggesting that empathy plays another role in preventive health behavior (i.e., vaccinate for the sake of protecting others) [ 77 ]. In conjunction with the present findings, we may also consider promoting the attachment quality of the public so that they will be more motivated to engage in preventive health behavior [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under COVID-19 conditions, how to prevent health behavior (e.g., vaccination) is an important issue to be considered [ 76 ]. Besides personal factors such as beliefs and self-efficacy about preventive health behavior, there are views suggesting that empathy plays another role in preventive health behavior (i.e., vaccinate for the sake of protecting others) [ 77 ]. In conjunction with the present findings, we may also consider promoting the attachment quality of the public so that they will be more motivated to engage in preventive health behavior [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parents may play a crucial role in promoting adolescents' health behavior and mental health during COVID‐19. Therefore, in addition to personal factors that are related to adolescents' adjustment (e.g., empathic concern, Pfattheicher et al, 2020 ; Qu et al, 2022 ), it is also important to identify family contexts that play a role in adolescents' adjustment during the pandemic. With regard to the relationship between parents and adolescents, attachment is a fundamental bond that is key to adolescent development (Allen & Land 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on a short-term longitudinal study, Qu et al. [ 1 ] showed that empathy positively predicted preventive health behavior under COVID-19, such as maintaining social distancing and wearing a mask when going out, which highlights the importance of prosocial motivation in promoting health behavior to prevent COVID infection. While perspective taking and concern for personal health were not related to preventive behavior for COVID infection, empathic concern positively predicted preventive health behavior and COVID-19 worries.…”
mentioning
confidence: 99%
“…Finally, Qu et al. [ 1 ] highlighted the importance of understanding the role of altruistic motives in preventive health behavior under COVID-19. In a recent study, Christner et al.…”
mentioning
confidence: 99%